Application of constructed wetland systems to treat wastewaters containing perfluorinated compounds - Yanasinee Suma; Chongrak Polprasert; Preeda Pakpian; Suwanna Kitpati Boontanon; RTG Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2009)
This study was conducted to investigate the technical feasibility of applying of subsurface-flow constructed wetland (SFCW) in treating wastewaters contaminated with perfluorooctane sulfonate (PFOS) and perfluorooctanoate (PFOA). It was found from the experiments that hydraulic retention time (HRT) exhibited significant effects on the removal of PFOS and PFOA, chemical oxygen demand (COD) and total nitrogen (TN). The SFCW units operating at the HRT of 5 d yielded the highest treatment efficiencies with PFOS and PFOA removal of 65.1% and 64.5%, respectively. COD removal efficiencies of 92.3 % for the both PFOS or PFOA {u2013}fed units and TN removal efficiencies of 90.1% and 93.0 % for PFOS {u2013} fed units and PFOA {u2013} fed units, respectively. The first - order kinetic coefficient (k20) of both PFOS and PFOA removal were found to be 0.13 d -1, for COD removal in PFOS{u2013} fed units and PFOA {u2013} fed units were found to be 0.32 and 0.31 d -1, respectively, and for TN removal, they were found to be 0.31 and 0.35 d -1 for PFOS{u2013} fed units and PFOA {u2013} fed units, respectively. Based on adsorption capacities, the maximum capacities of PFOS and PFOA on sand and gravel media were found to be 0.259 and 0.016 mg PFOS or PFOA/g media, respectively, equivalent to theoretical amount PFOS or PFOA adsorbed of 6.61 g in each SFCW unit. Based on adsorption alone, the calculated breakthrough times of PFOS and PFOA fed to the SFCW units at the concentration of 5 mg/L would be 47, 97, 287 and 472 d if they were operated at the HRT of 0.5,1, 3 and 5 d, respectively. Mass balance analysis showed that most of the PFOS at the long HRT of 5 d were removed by the SFCW unit through adsorption on the SFCW media (61.36 %), while much less were removed by cattail plant uptake (1.87 %) and precipitation, filtration and biodegradation (1.81 %); and the effluent outflow accounted for 34.96 %. Most of the PFOA at the long HRT of 5 d were removed by the SFCW unit through adsorption on the SFCW media (59.68 %), while the less were removed by cattail plant uptake (2.21 %) and precipitation, filtration and biodegradation (2.71 %) and the effluent outflow accounted for 35.41 %. Overall, this study demonstrated the technical feasibility applying CW to treat wastewaters containing PFOS and PFOA compounds which should help to reduce contamination of these compounds in the environment and minimizing health risks to humans.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Environmental Engineering and Management
Thesis (M.Sc.) - Asian Institute of Technology, 2009
Keywords: Constructed wetlands; Perfluorooctanoic acid; Sewage -- Purification